Economic choices 1987 - Aaron, Henry J. (Washington, D.C. : Brookings Institution, 1986)
In this book, six Brookings economists take a new look at the state of the economy, the budget deficit, and the budget process. They present a new plan for reducing the deficit, a plan they believe is preferable to either the proposals made by the Reagan administration or the results of the Gramm- Rudman-Hollings procedures.
Includes bibliographical references.
rpm 19/06/2017
Loans
Keywords: Budget deficits; Deficit financing; Government spending policy; Budget; United States